2018
DOI: 10.1029/2018jd028974
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric Aerosols, Polar Stratospheric Clouds, and Polar Ozone Depletion After the Mount Calbuco Eruption in 2015

Abstract: We investigate the impact of the 2015 Mount Calbuco eruption and previous eruptions on stratospheric aerosols, polar stratospheric clouds, and ozone depletion using the Community Earth System Model coupled with the Community Aerosol and Radiation Model for Atmospheres compared with several satellite and balloon observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 70 publications
4
46
0
Order By: Relevance
“…This result is found to be in agreement with previous published results (e.g. Bègue et al, 2017;Shikwambana and Sivakumar, 2018;Zhu et al, 2018). Bègue et al (2017) showed that the latitudinal extent of the Calbuco plume was bounded by the subtropical barrier and the polar vortex.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is found to be in agreement with previous published results (e.g. Bègue et al, 2017;Shikwambana and Sivakumar, 2018;Zhu et al, 2018). Bègue et al (2017) showed that the latitudinal extent of the Calbuco plume was bounded by the subtropical barrier and the polar vortex.…”
Section: Methodssupporting
confidence: 93%
“…Zuev et al (2018) concluded that the cause of the abnormal stratospheric ozone depletion above the Antarctic during October and November was the behaviour of the polar vortex in that period. Through the analysis of the zonal average backscattering from CALIOP, Zhu et al (2018) showed that the Calbuco aerosols progressed 16 km toward the South Pole during June. Moreover, Bègue et al (2017) discussed the meridional spread of the Calbuco aerosols toward the South Pole, which was modulated by the Quasi-Biennial Oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Kovalev et al [48] provide a method to obtain the layer optical depth τ c in the situation where a layer is present for only part of the observation time, such as for the case of the short-lived lower layers in Figure 6a. Here τ c (z l : z u ) = 0.5 × ln {(P 1 (z l ) ÷ P 2 (z l )) ÷ (P 1 (z u ) ÷ P 2 (z u ))} (13) where P 1 and P 2 are the observed lidar signal at times 1 (without the layer) and 2 (with the layer, respectively. The relationship between the layer optical depth and transmission is τ c (z l : z u ) = −ln T c (z l : z u )…”
Section: Optical Depth and Lidar Ratiomentioning
confidence: 99%
“…Carn et al [9] estimated the flux of SO 2 into the upper-troposphere lower-stratosphere region from the eruption as 0.2 to 0.5 Tg, which placed the event as one of the largest in the Southern Hemisphere over the previous decade. The effects of the Calbuco aerosol plume were not confined to mid-latitudes and included the enhancement of ozone destruction over Antarctica during the austral spring of 2015 [10][11][12][13]. The characteristics of the Calbuco aerosol plume and its movement to southern high latitudes were described by Stone et al [12] from measurements by the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) lidar on the Cloud-Aerosol Lidar and Infrared pathfinder Satellite (CALIPSO) satellite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation